On the Origin of the Green Colour of Archaeological Bone Artefacts of the Gallo‐Roman Period. (6th June 2013) - Ferrand, J.; Rossano, S.; Rollet, Ph.; Allard, T.; Cordier, P.; Catillon, G.; Auxiette, G.; Farges, F.; Pont, S.
<x xml:space="preserve">Abstract</x> Recent findings in the city of Reims have lead to the discovery of manufactured bone objects coloured in green throughout their entire volume. In order to discover the intentional nature of the colouration and to propose a colouration mechanism, modern ox bones have been coloured in the laboratory. Bones with a hue similar to that of the archaeological artefacts have been obtained by boiling in an acidic brine in a copper vessel. A combination of infrared spectroscopy, X‐ray diffraction and transmission electron microscope observations did not reveal the speciation of copper, but allowed us to validate the colouration process and to discuss the intentional origin of the colouration.